Chemical Constituents from the Roots of Clausena excavata and Their Cytotoxicity - Tawanun Sripisut (2018)
Six coumarins (1-6) and twelve alkaloids (7-18) were isolated from the roots of Clausena excavata. Their structures were elucidated on the basis of spectroscopic methods. This is the first report on the isolation of compounds 1, 7 and 17 from C. excavata. Compound 1 is also the first example of an unsymmetrical dimer coumarin isolated from Clausena species. The completed assignment of13C NMR spectral data of 1 as well as HMBC spectral data is also reported here for the first time. Compounds 2-7, 11-16 and 18 were evaluated for their cytotoxicity against three human cancer cell lines, oral cavity cancer (KB), breast cancer (MCF7) and small cell lung cancer (NCI-H187). The results showed that compounds 4, 11 and 18 exhibited highest cytotoxicity against KB, MCF7 and NCI-H187 cell lines with IC50 values of5.95, 3.76 and 5.65 μg/mL, respectively. © 2012 Reproduction is free for scientific studies.